Evaluation of the Implementation of Competency Certification Tests for Students in the Multimedia Expertise Program by LSP-P1 at SMK Negeri 40 Jakarta Using the CIPP Evaluation Model - Dahlia Safarinah (PT. Anagata Sembagi Education, 2025)
This study aims to evaluate the implementation of competency certification tests for students in the multimedia expertise program at SMK Negeri 40 Jakarta, using the CIPP evaluation model (Context, Input, Process, Product, Outcome). The research employs both descriptive quantitative and qualitative approaches, involving data collection through questionnaires, interviews, and observations. The respondents include students, assessors, and other stakeholders. The findings indicate that the implementation of competency certification tests at SMK Negeri 40 Jakarta faces several challenges. In terms of context, there is alignment between the program's objectives and industry needs; however, there is still room for improvement. Regarding input, the quality of human resources and infrastructure is considered adequate, although some facilities require enhancement. The process of implementing the certification tests shows that the procedures applied are appropriate, but supervision needs to be strengthened. Concerning the product, the certification test results indicate a good graduation rate, but the documentation of results requires improvement. Finally, from the outcome perspective, this program provides significant benefits for students, although the long-term impact on graduates' careers still needs further investigation. In conclusion, while the implementation of competency certification tests at SMK Negeri 40 Jakarta is progressing well, several aspects still require improvement to enhance the effectiveness and relevance of the program in meeting labor market needs. Recommendations for improvement are suggested to further optimize this program.